Prescription patterns in patients with schizophrenia in Japan: First‐quality indicator data from the survey of "Effectiveness of Guidelines for Dissemination and Education in psychiatric treatment (EGUIDE)" project - Kayo Ichihashi; Hikaru Hori; Naomi Hasegawa; Yuka Yasuda; Tomoya Yamamoto; Takashi Tsuboi; Kunihiro Iwamoto; Taishiro Kishimoto; Tadasu Horai; Hiroki Yamada; Nobuhiro Sugiyama; Toshinori Nakamura; et al. (Wiley, 2020)
Abstract Background Guideline for Pharmacological Therapy for Schizophrenia was published by the Japanese Society of Neuropsychopharmacology in 2015. "Effectiveness of Guidelines for Dissemination and Education in psychiatric treatment (EGUIDE)" project aimed to standardize medical practice using quality indicators (QIs) as indices to evaluate the quality of medical practice. In this study, we have reported the quality indicator values of prescription before the beginning of the guideline lectures in the EGUIDE project to ascertain the baseline status of treating patients with schizophrenia. Methods A cross‐sectional, retrospective case record survey was conducted, involving 1164 patients with schizophrenia at the time of discharge. We checked all types and dosage of psychotropic drugs. Results Forty‐three percent of patients had antipsychotic polypharmacy, and substantial concomitant medication was observed (antidepressants; 8%, mood stabilizers: 37%, anxiolytics or hypnotics: 68%). Conclusions In the results obtained in this study, we plant to report changes in the effectiveness of education in the EGUIDE project near the future.